Basic Sanitation as a Key Determinant of Diarrhea Among Under‑Five Children - Pilipus Pilipus; Apriyani Apriyani; I Putu Sukra (FORIKES, 2026)
Basic sanitation represents fundamental efforts to improve human health by ensuring the availability of a clean and safe environment. Core components of basic sanitation include access to clean water, household latrines, solid‑waste disposal facilities, and domestic wastewater drainage systems. Inadequate sanitation infrastructure is widely recognized as a major contributor to diarrheal diseases, particularly among vulnerable groups such as under‑five children. This study aimed to analyze the relationship between household waste‑bin conditions and latrine conditions with the incidence of diarrhea among under‑five children in the Baqa Primary Health Center area, Samarinda, in 2023. A quantitative approach with a cross‑sectional design was employed. The study involved 96 respondents selected through observational assessment. Data collection utilized structured observation sheets (checklists) to evaluate household waste‑bin conditions, latrine conditions, and diarrheal incidence among under‑five children. Data analysis was conducted using the Chi‑square test and Fisher’s Exact Test as an alternative when assumptions were not met. The findings indicated a significant association between household waste‑bin conditions and diarrheal incidence among under‑five children (p = 0.002). A significant relationship was also found between latrine conditions and diarrheal incidence (p = 0.000). These results suggest that inadequate waste‑bin facilities and substandard latrine conditions contribute to a higher risk of diarrhea among toddlers. In conclusion, improving household sanitation, particularly by providing proper waste‑bin facilities and ensuring latrines meet health standards is essential to reducing diarrheal incidence among under‑five children. Strengthening community awareness and promoting compliance with sanitation requirements are recommended to minimize disease occurrence.Keywords: under‑five children; basic sanitation; waste‑bin condition; latrine condition; diarrhea incidence